2021
DOI: 10.1111/1365-2745.13726
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant–pollinator interactions in structuring nectar microbial communities

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 111 publications
(206 reference statements)
3
31
0
Order By: Relevance
“…They are probably nectar/pollen robbers, as they were not observed eating floral organs. However, in a study on microbial communities in flower nectar, de Vega et al (2021) [57] found that plants visited by beetles supported the highest richness and phylogenetic diversity of yeasts, and bacteria communities compared to flowers visited by pollinators like bees. This suggests that the inhabiting of these tiny beetles in flowers may change the nectar attributes, and consequently influence interactions between flowers and their legitimate pollinators.…”
Section: Uncertain Roles Of Flower Visiting Beetlesmentioning
confidence: 99%
“…They are probably nectar/pollen robbers, as they were not observed eating floral organs. However, in a study on microbial communities in flower nectar, de Vega et al (2021) [57] found that plants visited by beetles supported the highest richness and phylogenetic diversity of yeasts, and bacteria communities compared to flowers visited by pollinators like bees. This suggests that the inhabiting of these tiny beetles in flowers may change the nectar attributes, and consequently influence interactions between flowers and their legitimate pollinators.…”
Section: Uncertain Roles Of Flower Visiting Beetlesmentioning
confidence: 99%
“…Nectar microbes frequently engage in competition for resources, often excluding one another via niche preemption or modification [91]. Despite such documented priority effects [20,23,35] and individual flowers being observed to be dominated by individual species [22], surveys of floral nectar have also revealed frequent co-occurrence of microbes (but see [92]). For example, positive associations have been detected between Metschnikowia yeasts and Acinetobacter bacteria [48] .…”
Section: Current Research and Future Directions On Nectar Microbe Eff...mentioning
confidence: 99%
“…However, the health of other invertebrate and vertebrate pollinators (figure 2b) that depend on nectar may also be sensitive to nectar microbes, the chemical changes they induce, and other potential mechanisms discussed. This is especially true given increasing evidence for both the likelihood and frequency for such interactions to occur, as surveys of flowers pollinated by these guilds have revealed that they may harbour abundant and diverse microbial communities [17,92,121]. Among insects, many species in the orders Coleoptera, Diptera, Hymenoptera, and Lepidoptera visit flowers to procure nutritive and non-nutritive rewards.…”
Section: (E) Effects Of Nectar Microbes On Lesser-studied Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study system here consists of the bacteria and yeasts that colonize the floral nectar of the sticky monkeyflower, Diplacus (formerly Mimulus ) aurantiacus , a hummingbird-pollinated shrub native to California and Oregon of the USA (Belisle et al ., 2012). Initially sterile, floral nectar in individual flowers is colonized by these microbes via pollinator-mediated dispersal (Belisle et al ., 2012; de Vega et al ., 2021). Microbial communities that develop in nectar though this dispersal are often simple, dominated by a few species of specialist bacteria or yeast (Álvarez-Pérez et al ., 2019; Golonka & Vilgalys, 2013; Herrera et al ., 2010; Tsuji & Fukami, 2018; Warren et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%